Central and Eastern European Literary Theory and the West - Mrugalski, Michał; Schahadat, Schamma; Wutsdorff, Irina (De Gruyter Reference, 2022)
The twentieth century saw intensive intellectual exchange between Eastern and Central Europe and the West. Yet political and linguistic obstacles meant that many important trends in East and Central European thought and knowledge hardly registered in Western Europe and the US. This book uncovers the hidden westward movements of Eastern European literary theory and its influence on Western scholarship.